Health costs of low intensity level violent and non-violent conflicts in Pakistan - Sajjad Ahmad Jan; Muhammad Wasif Siddiqi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
The immediate health cost of violent armed conflict is in the form of deaths and injuries of the combatants as well as civilians. However, these costs are mostly pertinent to major violent internal and international conflicts. Minor violent armed conflicts and nonviolent/ latent conflicts do not have as much capacity to kill and injure. However, these conflicts do have the capacity to affect human health in the long run through some less obvious channels. Diversion of resources from health sector to military and changes in the priorities of state and its institutions severely restrict the state's capacity and willingness to provide health facilities and the people's capacity to avail these facilities. In this study, the effect of Pakistan's internal conflict and Pakistan-India conflict on the health of people in Pakistan is analyzed during 1972-2004. Pakistan's internal conflict and the conflict with India during 1972-2004 are minor violent and non-violent/latent conflicts and it is more probable that these conflicts may affect people's health through these less obvious channels instead of killings and destruction.
Keywords: 330; conflict; internal conflict; Pakistan-India conflict; health index; institutions; military expenditure